The prevalence of cardiovascular disease is higher in patients with bilateral low ankle-brachial index than in patients with unilateral low ankle-brachial index. (November 2022) - Maruhashi, Tatsuya; Kajikawa, Masato; Kishimoto, Shinji; Yamaji, Takayuki; Harada, Takahiro; Hashimoto, Yu; Mizobuchi, Aya; Tanigawa, Shunsuke; Yusoff, Farina Mohamad; Nakano, Yukiko; Chayama, Kazuaki; Nakashima, Ayumu; et al.
Abstract: Background and aims: Ankle-brachial index (ABI) has been used as a vascular marker of atherosclerosis for cardiovascular risk assessment. However, it is unclear whether there is a difference in cardiovascular risk between patients with low ABI (<1.00) in one leg (unilateral low ABI) and patients with low ABIs in both legs (bilateral low ABI). Therefore, we investigated the associations of cardiovascular disease (CVD) with unilateral low ABI and bilateral low ABI to determine whether cardiovascular risk is higher in patients with bilateral low ABI than in patients with unilateral low ABI. Methods: We measured ABI in 2226 subjects. Results: The prevalence of CVD was higher in patients with bilateral low ABI than in individuals with normal ABI (1.00–1.40) and patients with unilateral low ABI (49.2%, 25.7% and 17.0%, respectively; p < 0.001). Multivariate analysis revealed that bilateral low ABI was significantly associated with an increased risk of CVD (OR, 2.30; 95% CI, 1.16 to 4.54; p = 0.02), whereas there was no significant association between unilateral low ABI and CVD (OR, 0.83; 95% CI, 0.47 to 1.46; p = 0.51). Propensity score matching analysis showed that the prevalence of CVD was significantly higher in patients with bilateral low ABI than in patients with unilateral low ABI (45.5% vs. 27.3%, p = 0.02). Conclusions: Cardiovascular risk may be higher in patients with bilateral low ABI than in patients with unilateral low ABI. More attention should be paid to whether a low ABI is present in one leg or in both legs for more precise cardiovascular risk assessment. Graphical abstract: Image 1 Highlights: ・Ankle-brachial index (ABI) has been used for cardiovascular risk assessment. ・Bilateral low ABI is associated with an increased risk of concomitant cardiovascular (CV) disease. ・Unilateral low ABI is not associated with an increased risk of CV disease. ・Attention should be paid to whether a low ABI is present in one leg or in both legs.